Potential thermostable mutants of endoglucanase I from fusarium oxysporum - Ibrahim Ali , Noorbatcha; Hamzah, Mohd. Salleh (2015)
Lignocellulose is the most abundant biopolymer on earth and it is a good renewable energy source. Thermostable enzymes have several benefits in various industrial applications. Among the benefits are they allow the use of increased substrate concentration in the reaction mixture, as the viscosity will drop at higher temperature which eventually will improve product yield and reduces capital and processing costs. This research intends to predict computationally, and develop experimentally, a thermostable mutant endoglucanase that can operate at higher temperature as required by industrial processes. Our preliminary computational data based on rational design approach suggest that quintuple mutant, T224E/G229A/S230F/S231E/N321R, of an endoglucanase from a pathogenic fungus, Fusarium oxysporum, can potentially remain active at higher temperature (80oC) compared to its current operating temperature (<60oC). In our effort to experimentally produce this quintuple mutant we have successfully produced a single mutant, T224E, and a triple mutant, G229A/S230F/S231E, via site directed mutagenesis. We are reporting here the characterization results of these two mutants as compared to the wild type.